The Causal Relationship Between Asthma and Hippocampal Volume: A Study Based on Bidirectional Mendelian Randomization Analysis - Dandan Han; Shaohua Zhao (Brain and Behavior)
ABSTRACT Background Asthma is a common chronic respiratory disease, and its potential association with the central nervous system has garnered increasing attention in recent years. While observational studies suggest that asthma may affect hippocampal structure and function through mechanisms such as chronic inflammation and hypoxia, its causal relationship remains unclear. Methods In this study, we employed a two‐sample Mendelian randomization (MR) analysis, utilizing large‐scale genome‐wide association study (GWAS) data to systematically investigate the potential causal relationship between asthma and hippocampal volume. Data from a GWAS of asthma involving 155,386 individuals of European ancestry and GWAS imaging‐derived phenotypes (IDPs) of hippocampal volume from 33,219 European individuals were analyzed. Results The results revealed a significant negative correlation between asthma and multiple hippocampal IDPs (PFDR < 0.05), indicating that asthma may contribute to reduced hippocampal volume. We identified 19 independent SNPs significantly associated with asthma (P < 5×10⁻⁸), of which 16 SNPs were retained after clumping (r2 < 0.001) and harmonization. Sensitivity analyses revealed no heterogeneity or horizontal pleiotropy, and reverse MR analysis did not support a causal effect of hippocampal volume on asthma. Conclusion Our study provides genetic evidence for a causal relationship between asthma and changes in hippocampal volume, highlighting the need for closer monitoring and intervention in the neurocognitive health of asthma patients in clinical practice. Future studies should explore the causal relationship between asthma and brain structural changes across different racial groups and asthma subtypes, as well as the underlying biological mechanisms.